Recreational forest landscape development: a strategy for managing forest resources in sustainable manner in Malaysia - Hussein, Mohd Kher (Science Events, 2014)
Natural forests have unique and beautiful landscape that meets recreation and ecotourism needs. They provide places for people to carry out activities such as recreation and nature appreciation. Many governments in the world have established Recreational Forests as a strategy to conserve and manage the areas concerned. However, how much the forest parks have been developed in a sustainable manner is still argued. Objective of this study is to understand the sustainability of recreational forest landscape and to analyze the current development towards sustainability. Approach of the study was based on literature review and case study. This study shows that the development of recreational forest landscape meets the concept of conservation, but fails to fulfill the concept of sustainability. Thus, knowledge and understanding on the concept of forest landscape sustainability need to be improved in recreational forest landscape development process for the sake of our fragile forest environment and future generation.